Investing in the future: lessons learnt from communicating the results of HSV/ HIV intervention trials in South Africa - Mayaud Philippe; Stadler Jonathan; Delany-Moretlwe Sinead; Rees Helen (BMC, 2011)
Abstract Background Communicating the results of randomised controlled trials may present challenges for researchers who have to work with communities and policy-makers to anticipate positive outcomes, while being aware that results may show no effect or harm. Methods We present a case study from the perspective of researchers in South Africa about the lessons learnt from communicating the results of four trials evaluating treatment for herpes simplex virus type 2 (HSV-2) as a new strategy for HIV prevention. Results We show that contextual factors such as misunderstandings and mistrust played an important role in defining the communications response. Use of different approaches in combination was found to be most effective in building understanding, credibility and trust in the research process. During the communication process, researchers acted beyond their traditional role of neutral observers and became agents of social change. This change in role is in keeping with a global trend towards increased communication of research results and presents both opportunities and challenges for the conduct of future research. Conclusions Despite disappointing trial results which showed no benefit of HSV-2 treatment for HIV prevention, important lessons were learnt about the value of the communication process in building trust between researchers, community members and policy-makers, and creating an enabling environment for future research partnerships.